Sphères publiques et représentations sociales du vaccin - Sandrine Gaymard; Romain Hidrio (Communication)
The medical bodies promoting vaccination and raising global awareness of its benefits still have a lot of work to do. To understand the situation, the authors conducted a psychology study on the social representation of vaccination in France using a three-part, mixed methodology survey. The survey was posted on Facebook from March to June 2019, specifically on group pages for people who identify as anti-vaxxers and group pages for people who identify as “neutral”.